An advanced tabu search approach to the dynamic airlift loading problem - August G. Roesener; J. Wesley Barnes (Logistics Research, 2016)
This research effort presents a tabu search algorithm to solve the dynamic airlift loading problem. Given a set of palletized cargo items which require transportation from an aerial port of embarkation to an aerial port of debarkation within a pre-specified time frame, the dynamic airlift loading problem seeks to partition the pallets into aircraft loads, select an efficient and effective subset of aircraft from available aircraft, and assign the pallets to allowable positions on those aircraft. The dynamic airlift loading problem differs from many partitioning and packing problems described in the literature because, in addition to spatial constraints, factors such as allowable cabin load, balance restrictions, and temporal restrictions on cargo and aircraft are included. The algorithm developed in this research, the dynamic airlift loading problem-tabu search, was tested on a variety of problem instances. Since real-world solutions are hand generated by subject matter experts and no previous research effort has solved this specific problem, the algorithmic results are compared to compute lower bounds on the number of aircraft trips required.
Keywords: 650; Tabu search; Knapsack; Bin packing; Military applications; Aircraft loading